1939
DOI: 10.1017/s002202990000296x
|View full text |Cite
|
Sign up to set email alerts
|

232. A simple and accurate viscosimetric form of rennet test

Abstract: 1. Some existing types of rennet tests are briefly reviewed.2. A viscosity type of rennet test is described and results from its use are given.3. A mathematical treatment of the problems involved is given, which leads on to4. Construction of graphs showing progressive variation in “Dying away of amplitude”, “Logarithmic decrement” and “Viscosity coefficients” of milk under the action of rennet. Since viscosity determinations on liquids and gases have been commonly carried out with a disk type of viscosimeter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1940
1940
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Following 5 min. of stirring, the solution was brought to pH [6][7][8] with N/1 NaOH and then heated quickly to 80° C. to inactivate native proteases of the milk (13). This process generally removed the alcohol and acetone and brought into solution any undissolved particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following 5 min. of stirring, the solution was brought to pH [6][7][8] with N/1 NaOH and then heated quickly to 80° C. to inactivate native proteases of the milk (13). This process generally removed the alcohol and acetone and brought into solution any undissolved particles.…”
Section: Methodsmentioning
confidence: 99%
“…Viscometric analyses have been used to measure the rate of clotting of milk (3,4,5,6,7) and to gain specific information about the phases of the renneting processes. On the basis of viscometric study of solutions of casein in NaOH, Jirgensons (8) suggested that casein particles decreased in symmetry (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an automatic coagulation time recorder was developed modelled on the principle used by Randall (2) in an apparatus for testing heparin. This instrument promised considerable advantages in convenience and accuracy over previously described forms of apparatus (3,4,5,6,7,8,9).…”
Section: Introductionmentioning
confidence: 99%